2016
DOI: 10.1155/2016/4680972
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Resting-State Functional Connectivity Strength in Mild Cognitive Impairment and Its Conversion to Alzheimer’s Disease

Abstract: Individuals diagnosed with mild cognitive impairment (MCI) are at high risk of transition to Alzheimer's disease (AD). However, little is known about functional characteristics of the conversion from MCI to AD. Resting-state functional magnetic resonance imaging was performed in 25 AD patients, 31 MCI patients, and 42 well-matched normal controls at baseline. Twenty-one of the 31 MCI patients converted to AD at approximately 24 months of follow-up. Functional connectivity strength (FCS) and seed-based function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 61 publications
12
38
1
Order By: Relevance
“…At the global brain level, we found that MCI patients had weaker functional connections in the brain network, which was consistent with previous functional network studies of AD (Li et al, 2016) and MCI (Wang et al, 2013;Lee et al, 2016). Some results demonstrated that these abnormal functional connections were directly related to the global topological attributes of brain networks (Wang et al, 2013).…”
Section: Altered Pattern Of the Brain Network Connectome In MCIsupporting
confidence: 90%
“…At the global brain level, we found that MCI patients had weaker functional connections in the brain network, which was consistent with previous functional network studies of AD (Li et al, 2016) and MCI (Wang et al, 2013;Lee et al, 2016). Some results demonstrated that these abnormal functional connections were directly related to the global topological attributes of brain networks (Wang et al, 2013).…”
Section: Altered Pattern Of the Brain Network Connectome In MCIsupporting
confidence: 90%
“…The T2DM-specific pattern of reduced CBF (in posterior and anterior regions) is very similar to the pattern observed in patients with MCI and Alzheimer’s disease (AD) (Li et al 2016; Mevel et al 2011). Moreover, in the current study the T2DM-specific pattern of reduction in CBF was associated with insulin resistance, mobility function, and executive function.…”
Section: Discussionsupporting
confidence: 67%
“…The present study confirms prior findings of reduced functional connectivity in disparate regions of the DMN network in MCI relative to cognitively healthy controls (Bai et al, ; Chhatwal & Sperling, ; De Vogelaere, Santens, Achten, Boon, & Vingerhoets, ; Jin, Pelak, & Cordes, ; Li et al, ; Sorg et al, ; Weiler et al, ), while extending this line of work to demonstrate that regional connectivity patterns differed both within and between groups as a function of WMSA volume and cortical thickness. Both structural measures differentially influenced group differences in functional connectivity between the precuneus‐seed region and the LTC, IPL, and pCC, with WMSA exhibiting the strongest effect on DMN connectivity within mPFC regions.…”
Section: Discussionsupporting
confidence: 91%